Differences in sentence complexity in the text of children's picture books and child-directed speech. Issue 5 (October 2019) - Montag, Jessica L.
Reading picture books to pre-literate children is associated with improved language outcomes, but the causal pathways of this relationship are not well understood. The present analyses focus on several syntactic differences between the text of children's picture books and typical child-directed speech, with the aim of understanding ways in which picture book text may systematically differ from typical child-directed speech. The analyses show that picture books contain more rare and complex sentence types, including passive sentences and sentences containing relative clauses, than does child-directed speech. These differences in the patterns of language contained in picture books and typical child-directed speech suggest that one important means by which picture book reading may come to be associated with improved language outcomes is by providing children with types of complex language that might be otherwise rare in their input.